The brick architecture of the governor’s palace in Aquincum - Havas, Zoltán (Dissertationes Archaeologicae, 2020)
Abstract of PhD thesis submitted in 2019 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Dénes Gabler.